2020
DOI: 10.1111/rode.12662
|View full text |Cite
|
Sign up to set email alerts
|

Wagner’s Law and Fiscal Illusion: An analysis of state government finances in Brazil

Abstract: The aim of this article is to analyze state-level public finances in Brazil. We examine the dynamics of governmental spending in a panel of 26 Brazilian states in search of evidence of Wagner's Law and Fiscal Illusion Hypothesis. For the period ranging from 2002 to 2015, three methodologies are applied: dynamic ordinary least squares (DOLS), fully modified ordinary least squares (FMOLS), and pooled mean group (PMG). The main empirical results found indicate that (1) there is strong evidence of Fiscal Illusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Such findings corroborate the State's attempt to discourage taxpayers from seeking information using combinations of constructs, as Prado andSilva (2020) explained. Corroborating this, Teixeira (2018) states that the lack of knowledge about how much taxpayers receive and pay to the State causes fiscal illusion.…”
Section: Based On the Results Found Insupporting
confidence: 59%
See 3 more Smart Citations
“…Such findings corroborate the State's attempt to discourage taxpayers from seeking information using combinations of constructs, as Prado andSilva (2020) explained. Corroborating this, Teixeira (2018) states that the lack of knowledge about how much taxpayers receive and pay to the State causes fiscal illusion.…”
Section: Based On the Results Found Insupporting
confidence: 59%
“…On the other hand, the public budget is a favorable space for developing fiscal illusion, influencing the size and quality of expenditures (Siqueira & Nogueira, 2014). Furthermore, biases in budget decisions are made by taxpayers because of underestimating the costs of public spending (Gemmell, Morrissey, & Pinar, 1999;Dell'anno & Dollery, 2014;Prado & Silva, 2020).…”
Section: Based On the Results Found Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Abatemarco and Dell'Anno (2020) revealed that an increase in the median voter's income can positively or negatively affect tax progressivity depending on the type (pessimistic or optimistic) of fiscal illusion. Prado & da Silva (2020) indicated that due to fiscal illusion, the less-developed Brazilian states tend to be stuck in a mechanism of public spending growth, especially in spending on non-public goods that tend to benefit private interests and lobby groups. In another study, Serrano et al (2022) concluded that the expansion of public spending in Brazil is partly due to fiscal illusion.…”
Section: Introductionmentioning
confidence: 99%